The Blackwell handbook of mediation : bridging theory, research, and practice - Herrman, Margaret S., 1944-; Blackwell Reference Online (Online service) (Malden, MA ; Oxford : Blackwell Pub., 2006)
This is an ideal text for graduate students of conflict resolution, problem solving or negotiation in departments of liberal arts, law and business schools as well as trainers and practitioners in the field.
Introduction / Margaret S. Herrman -- Mediation from beginning to end : a testable model / Margaret S. Herrman, Nancy Hollett, and Jerry Gale -- Examining mediation in context : toward understanding variations in mediation programs / Craig McEwen -- Policy, practice, and politics : bargaining in the shadow of Whitehall / Janet Walker and Sherrill Hayes -- The role of antecedent and procedural characteristics in mediation : a review of the research / Roselle L. Wissler -- Applying the comprehensive model to workplace mediation research / Brian Polkinghorn and E. Patrick McDermott -- Restorative justice mediated dialog / Mark S. Umbreit and Robert B. Coates -- Mediation as framing and framing within mediation / Barbara Gray -- Does the model overarch the narrative stream? / John M. Winslade and Gerald D. Monk -- A facework frame for mediation / Stephen Littlejohn and Kathy Domenici -- Mediation and the fourfold model of justice / Donald E. Conlon -- The dynamics of power in child custody mediation / Donald T. Saposnek -- Emotion in mediation : implications, applications, opportunities, and challenges / Tricia S. Jones -- Preempting disaster : pre-mediation strategies to deal with strong emotions / Daniel L. Shapiro -- The meaning of "social" in interpersonal conflict and its resolution / Sandra Schruijer and Leopold S. Vansina -- Manager as mediator : developing a conflict-positive organization / Dean Tjosvold and Fang Su -- Mediation and difficult conflicts / Morton Deutsch -- Enhancing mediator artistry : multiple frames, spirit, and reflection in action / Neil H. Katz -- Of time and the river : notes on the Herrman, Hollett, and Gale model of mediation / Kevin Avruch -- Mediation at the millennium / Dean G. Pruitt -- A trainer responds to the model / Zena D. Zumeta -- Conclusion / Margaret S. Herrman.
Includes bibliographical references and indexes.
Print version record.
English.
John Wiley and Sons
Keywords: Mediation -- Handbooks, manuals, etc; Negotiation -- Handbooks, manuals, etc; Conflict management -- Handbooks, manuals, etc; v; v; Gestion des conflits -- Guides, manuels, etc; v; SOCIAL SCIENCE -- Violence in Society; Conflict management; Mediation; Negotiation; Bemiddeling; Conflictmanagement; Mediation -- Guides, manuels, etc; Negociations -- Guides, mnauels, etc; Gestion des conflits -- Guides, manuels, etc; Handbooks and manuals